The Impact of COVID-19 on Banking Performance: Systematic Literature Review - Mukhtar (Management Science Research Journal, 2024)
A PRISMA-guided systematic literature review was conducted using purposive random Google searches to analyze research published from 2020 to 2024. This review included 9 types of study data from 52 identified studies. Design/methodology/approach – Analyzing the impact of COVID-19 on banking financial performance, carried out by reviewing the developing literature regarding the effects of COVID-19 on bank performance. The studies were selected based on the use of bank performance indicators in the form of financial performance ratios which were tested using the paired sample t-test or Wilcoxson z-test method, from 52 studies 9 indicators were selected with the most widely used namely ROA, CAR BOPO, LDR, NPL, ROE, NPF, FDR, NIM. Based on further testing using a one-sample t-test, the findings show that COVID-19 has no impact on the ROA indicator. CAR BOPO, NPL, NPF, FDR, while other indicators NIM, ROE, and LDR received the effects of Covid 19. The implications for the banking world and policymakers provide a more focused perspective in determining strategic performance. In contrast, the implications for further research provide new insights and questions about the extent to which these indicators explain the state of banking and its environmental conditions.